Unveiling the Impact of Naqshbandiyya Tariqa Values on Islamic Education: A Comprehensive Analysis of Pesantren Dar Al Ma'arif Kota Pinang - Yusra Dewi Siregar; Hasan Bakti Nasution; Junaidi Arsyad (STAI Hubbulwathan Duri, 2023)
This article discusses the internalization of the teachings of the Naqsyabandiyah Tariqa in Islamic educational institutions, specifically in the Dar Al Ma'arif Islamic boarding school in Pinang City, Sumatra. The study uses qualitative field research methods to examine the implementation of education and its impact on individuals and society. The findings suggest that the curriculum plays a crucial role in directing students towards competitiveness and awareness of the world's development. The study also highlights the importance of Tarekat Naqsyabandiyah's practices in creating a stable inner condition that leads to good social behavior. The article also discusses the spread of the Naqsyabandiyah Tariqa in the Malay region and the establishment of Pesantren Dar Al'Ma'arif as a center for Islamic education. The conclusion emphasizes the importance of pesantren in developing Islamic education and character building in Indonesia.